PENGEMBANGAN MEDIA PEMBELAJAARAN INTERAKTIF PADA MATA PELAJARAN MATEMATIKA POKOK BAHASA PENGUKURAN KELAS III SDN 85 KENDARI - Rismawati, Rismawati; Saputra, Hendra Nelva; Fajriani, Alfiah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Mathematics is often considered difficult by elementary school students, especially because of the abstract material delivery and lack of visualization. Based on the results of observations in grade III of SDN 85 Kendari, students experienced difficulties in understanding the concept of measurement, such as length, weight, and time. Conventional methods that are not supported by learning materials that do not interest students can lead to this. Therefore, it is very important for learning media that is easy to use, attracts students' interest, and is suitable for elementary school students. The goal is to create an interactive learning media with measurement materials using the Articulate Storyline 3 application and conduct an assessment of its feasibility and practicality. The stages of this research process began with the analysis, design, development, implementation, and evaluation stage, which is the ADDIE model in the Research and Development (R&D) method The results of validation by three media experts with an average score of 78.89%